Institutional dynamics produce resource curse traps - Nusrat Molla; Simon A. Levin; Elke U. Weber (Proceedings of the National Academy of Sciences, 2026)
Communities reliant on extractive industries face a paradox: Despite the promise of economic growth from lucrative, well-paying industries, they often experience poor socioeconomic outcomes. While the so-called “resource curse” has been debated and studied extensively in a variety of disciplines, understanding when and why the resource curse occurs, and whether it is possible to escape it, remains a challenge. This study examines these questions through a dynamical systems model that incorporates theories from the literature about how extractive industries interact with institutions and the communities in which they are based. The model reveals that both the resource curse and a more diversified economy are possible, depending on the initial level of human and social capital. It also reveals how various factors, such as declining commodity prices, can trigger an abrupt and irreversible transition from the diversified equilibrium to the resource curse. A generalized version of the model further reveals that the feedback between extractive industries and institutional strength are critical in determining the occurrence of this type of transition. The results illustrate the difficulty of escaping the resource curse, identify potential leverage points or change, and highlight the critical role of institutional dynamics in producing and perpetuating extractive dynamics in these regions.